Association of Serum Galectin-3-Binding Protein and Metabolic Syndrome in a Chinese Adult Population - Zhen, Shihan; Cai, Ruoxin; Yang, Xuelian; Ma, Yanan; Wen, Deliang (Frontiers in Endocrinology, 2021)
Abstract Background: Galectin-3-binding protein (GAL-3BP) is a ubiquitous and multifunctional secreted glycoprotein, which functions in innate immunity and has been highlighted as a potential mediator of adipose inflammation in obesity. In this study, we aimed to identify whether GAL-3BP is a novel biological marker for metabolic syndrome (MetS). Methods: The biochemical and anthropometric variables of the 570 participants in this study were evaluated using standard procedures. Their serum GAL-3BP levels were measured using enzyme-linked immunosorbent assay (ELISA), while the association between the glycoprotein and MetS was analyzed using multiple logistic regression analyses. Moreover, an experimental MetS model was established. The expression of GAL-3BP in serum and adipose tissue was measured using ELISA and western blotting. Lipid accumulation was determined with the use of immunohistochemistry and immunofluorescent staining. Results: The serum GAL-3BP level was found to be positively associated with MetS. The logistic regression analyses demonstrated that participants expressing the upper levels of GAL-3BP were more likely to develop MetS than those expressing less of the glycoprotein (OR = 2.39, 95%CI: 1.49, 3.83). The association between the serum GAL-3BP level and MetS was found preferentially in postmenopausal women (OR = 2.30, 95%CI: 1.31, 4.05). In addition, GAL-3BP was increased in the serum and visceral adipose tissue (VAT) of high fat diet (HFD) mice. Moreover, GAL-3BP was highly expressed in VAT macrophages. Conclusions: This study confirmed serum GAL-3BP to be positively associated with MetS, highlighting it as a useful biological marker of MetS in Chinese participants.